Neonatal Microsurgical Repair of a Congenital Abdominal Aortic Aneurysm with a Cadaveric Graft - Annie Le-Nguyen; Shahrzad Joharifard; Geneviève Côté; Daniel Borsuk; Rafik Ghali; Michel Lallier (Georg Thieme Verlag KG, 2021)
Congenital abdominal aortic aneurysms (AAA) are an extremely rare entity. We present the case of a female fetus diagnosed with an AAA on routine prenatal ultrasound. A postnatal computed tomography angiogram revealed an infrarenal AAA with a narrow proximal neck. Surgery was performed on day of life 14 using a cadaveric femoral artery graft. The proximal anastomosis was performed under the microscope given the severity of the aortic stenosis and the proximity of the renal arteries. The patient's postoperative course was uneventful and she is developing normally 1 year after surgery. The graft remains permeable, albeit with evidence of proximal and distal stenosis and graft calcification on imaging.